Overview of research status of the problem of transportation of oversized cargoes in ukraine (Transport systems and technologies, 2019)
The transport industry, in addition to the traditional function of providing security for various spheres of the economy, is now becoming an independent transport and logistics mechanism that is developing more intensively due to the development of on-line and off-line commercial activities, the development of wholesale companies and warehousing activities, access to external markets, etc. Oversized cargo includes a group of goods that due to their size or weight can not be transported in an open or closed body or in containers, with parametric characteristics exceeding the established standards. The specific features of oversized cargo are their uniqueness, which causes the attraction of special equipment, additional route optimization, obtaining special permits and, if necessary, providing support services and the selection of drivers who have the appropriate qualification, etc. The main purpose of this article is to analyze the current state of study of the problem of oversized cargo transportation in Ukraine. During the study, methods such as: abstraction, analysis and synthesis, induction and deduction methods, etc. were used. The article describes the state of the study of the problem of transportation of oversized cargoes in Ukraine, in particular, the views of scientists on this issue are analyzed. The features of transportation of oversized cargo on river and sea transport are characterized. The circumstances, which are characterized by the state of affairs in the industry, are revealed. In addition, the views of scientists on the main unresolved issues characteristic of the transport industry in Ukraine as a whole and the transportation of oversized cargo in particular are analyzed. The author's vision for solving the identified problems and overcoming the existing difficulties in the industry is proposed. Thus, many scientists are investigating the problems of this industry, trying to identify the problems and disadvantages of the mechanisms of transportation of oversized cargo in Ukraine, with the prospect of further research is the development of modern models of the management of oversized cargo transportation in Ukraine using river and sea transport.
Keywords: transport, transport system, freight transport, river transport, sea transport, oversized cargo, oversized transportation